How to read a paper involving artificial intelligence (AI) - Trisha Greenhalgh; Jessica Morley; Paul Dijkstra; Yosra Magdi Mekki (BMJ Medicine)
This paper guides readers through the critical appraisal of a paper that includes the use of artificial intelligence (AI) in clinical settings for healthcare delivery. A brief introduction to the different types of AI used in healthcare is given, along with some ethical principles to guide the introduction of AI systems into healthcare. Existing publication guidelines for AI studies are highlighted. Ten preliminary questions to ask about a paper describing an AI based decision support algorithm are suggested.